Detailing Prevention Recommendations From the RNAO Best Practice Guideline - Pressure Injury Management: Risk Assessment, Prevention, and Treatment, Fourth Edition - Stade, Brenda; Burt, Amy; Nizum, Nafsin; Howitt, Lyndsay; Zucal, Giulia; Heerschap, Corey; Beeckman, Dimitri (Canadian Journal of Wound, Ostomy and Continence, 2026)
Background Pressure injuries (PIs) constitute some of the costliest adverse events in hospitals, in long-term care facilities, and in homecare settings. PIs are painful and can impact quality of life. Depending on the stage of the injury and whether there are complications or comorbidities, healing may take weeks, months, or years and can contribute to premature mortality. The Registered Nurses’ Association of Ontario (RNAO) released a best practice guideline (BPG) in November 2024 with evidence-based recommendations on the assessment, prevention, and treatment of PIs. This paper focuses on the prevention of PIs that are outlined in this guideline. Methods Best practice guidelines are based on systematic reviews and developed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. A panel of PI experts was convened to guide the process. We conducted a systematic literature review focusing on three preventive areas as related to PIs: repositioning frequency, care bundles, and use of prophylactic dressings. We searched seven databases for relevant English-language studies published since January 2018. Two reviewers independently assessed the research for eligibility and for risk of bias and determined the validity of the evidence using the GRADE approach. Results We screened 1,295 articles for 3 priority research questions. Of these articles, 234 full-text publications were reviewed for relevance, and 14 were used to inform 3 recommendations on repositioning frequency, preventive care bundles, and the use of prophylactic dressings. Conclusion This paper provides nurses and other members of the interprofessional team, including persons and their families, with evidence-based recommendations for preventing PIs.